PS 17-40 RELATIONS OF BLOOD PRESSURE VARIABILITY TO LEFT VENTRICULAR FUNCTION AND ARTERIAL STIFFNESS IN THE HYPERTENSIVE PATIENTS. (September 2016) - Shin, Sung-Hee; Jang, Ji-Hoon; Lee, Man-Jong; Park, Sang-Don; Kwon, Sung-Woo; Woo, Seong-Ill; Kim, Dae-Hyeok; Kim, Moon-Jae; Park, Keum-Soo; Kwan, Jun
Abstract : Objective: We examined the impacts of daytime systolic BP variability on left ventricular (LV) function and arterial stiffness in the hypertensive patients. Design and method: Ambulatory BP monitoring (ABPM) and echocardiography were performed in 116 hypertensive patients. We assessed BP variability as standard deviation of daytime systolic BP on the 24 hour ABPM. Conventional echocardiographic parameters as well as area strain using 3D speckle tracking were measured. Arterial stiffness was evaluated by acquiring pulse wave velocity (PWV) and augmentation index (AIx). Results: The patients with higher BP variability showed significantly increased LVMI and A velocity, and decreased E/A ratio, and area strain than those with lower BP variability (p = 0.02 for LVMI; p < 0.001 for A velocity; p < 0.001 for E/A ratio; p = 0.02 for area strain). In addition, increased BP variability was associated with higher PWV and AIx (p < 0.001). Even among the patients whose BP was well controlled, BP variability was related to LV hypertrophy, diastolic dysfunction and arterial stiffness. Conclusions: Increased BP variability was associated with LV hypertrophy and dysfunction as well as arterial stiffness, suggesting BP variability might be one of the important determinants of target organ damage in the hypertensive patients.